Menyalakan Kembali Nadi Hutan: Revitalisasi Kelompok Tani Hutan untuk Pemberdayaan dan Keberlanjutan Desa Mayanau Kabupaten Balangan - Fadillah; Ni'mah; Ramadhan, Muhammad; Al-Huda, Muhammad Hafiz; Amalia, Dinda Fitri; Nazwa, St Azizah; Nabila; Cahyani, Indah; Alifa, Aniq; Zarifa, Nur Amanda; Fauziah, Haya (Prodi Sosiologi FISIP ULM, 2025)
Community service in Mayanau Village, Tebing Tinggi Subdistrict, Balangan Regency, was carried out to revitalize the Forest Farmers Group (KTH) as a forum for sustainable forest management. Although Mayanau Village has vast forest potential with leading commodities in the form of non-timber forest products (NTFPs) such as rattan, forest honey, and medicinal plants, the two previous KTHs had become dormant. Weak management capacity, lack of legality, low community participation, and minimal synergy with external actors were the main causes of the institutional dysfunction. In addition, the institutional dysfunction of the Forest Farmers Group (KTH) has resulted in stagnant management of the village's natural resources. To that end, the service team implemented the “Revitalization of the Mayanau Village KTH Institution” program, which includes enabling, empowering, and protecting, using a live-in method for two months. This program was carried out through several activities, namely: 1) Mapping the root causes and potential problems; 2) Community awareness raising; 3) Joint discussions with the Forest Management Unit (KPH); 4) Formation of the KTH; 5) Institutional legalization process; and 6) Capacity building for administrators. The results of the program show the formation of a new KTH with an official structure, increased capacity of administrators, and initial community awareness of the importance of collective forest management. The revitalization program of the Forest Farmers Group (KTH) in Mayanau Village has succeeded in reviving the previously paralyzed institution through an enabling, empowering, and protecting approach. The relationship built with the Balangan Forest Management Unit (KPH) ensured the sustainability of the program through technical assistance and policy access. Through this program, it is believed that institutional strengthening, capacity building, and ecological awareness will become the foundation for the realization of sustainable community-based forest management in Mayanau Village.